GST: A Major Tax Reform Impacting Indian Businesses - Mittal , A. K. (Gyan Management Journal, 2016)
The Goods and Services Tax, one of the biggest reforms in India’s indirect tax structure, is likely to revolutionise the Indian economy in an unprecedented manner. As envisaged, GST will propel GDP growth to newer heights, lower income disparity and simplify decision making of businesses. The GST rollout will be a milestone for the nation as its implementation will have a far-reaching impact on the Indian economy. GST is a value-added tax levied at all points in the supply chain with credit allowed for any tax paid on input acquired for use in making the supply. It would apply to both goods and services in a comprehensive manner, with exemptions restricted to a minimum.